2020
DOI: 10.1111/jcmm.15829
|View full text |Cite
|
Sign up to set email alerts
|

LMNA functions as an oncogene in hepatocellular carcinoma by regulating the proliferation and migration ability

Abstract: The role of the LMNA gene in the development and progression of hepatocellular carcinoma (HCC) and the associated molecular mechanism is not yet clear. Therefore, the purpose of this study was to evaluate the relationship between LMNA and HCC. LMNA gene expression in normal tissues and corresponding tumours was evaluated and the Kaplan–Meier survival analysis was performed. Next, the LMNA gene was knocked out in the 293T and HepG2 cell lines using the CRISPR/Cas9 technique. Subsequently, the proliferation, mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 38 publications
(61 reference statements)
4
15
0
Order By: Relevance
“…In agreement with these works, in previous papers we also found that LMNA expression was related to a less malignant phenotype in human neuroblastoma [23,26]. By contrast, some studies revealed a link between increased LMNA expression and tumor progression in colorectal, prostate, ovarian and hepatocellular cancers [14,[31][32][33]. This ambiguity in the LMNA gene role as a cancer biomarker is probably due to the numerous diverse functions that Lamins perform in the cell and their variable expression between cancer subtypes [13].…”
Section: Discussionsupporting
confidence: 88%
“…In agreement with these works, in previous papers we also found that LMNA expression was related to a less malignant phenotype in human neuroblastoma [23,26]. By contrast, some studies revealed a link between increased LMNA expression and tumor progression in colorectal, prostate, ovarian and hepatocellular cancers [14,[31][32][33]. This ambiguity in the LMNA gene role as a cancer biomarker is probably due to the numerous diverse functions that Lamins perform in the cell and their variable expression between cancer subtypes [13].…”
Section: Discussionsupporting
confidence: 88%
“…44,45 Cells with low levels of lamin A have flexible nucleus and could easily compress through juxtaposed cells during migration; hence, the levels of lamin A in the nucleus is crucial to eventually ensure successful migration and cell survival. 46,47 Liu et al 48 showed that the migration ability of LMNA knockout cell lines in hepatocellular carcinoma (HCC) was significantly lower than that of the wild-type cells. Moreover, according to the authors, the LMNA gene was abnormally expressed in distinct cancer types and the survival rate of the HCC patients with a high expression of the LMNA gene was significantly reduced compared with the rate in patients with a low LMNA expression.…”
Section: Protein Relocation and Nuclear Proteins In The Secretome Of Tumoral Cellsmentioning
confidence: 99%
“…By subtyping analysis, to validate subtype biomarkers in HCC it was found up regulation of HSPA6 (heat shock proteins) associate with hepatocellular carcinoma and LMNA gene due to proliferation and migration ability function as an oncogene in HCC[31]. PPA2 which modulates histone methylation that interferes with p-53 induced apoptosis can be a marker gene for HCC.…”
Section: Discussionmentioning
confidence: 99%